Um olhar inédito sobre Francisco I numa fonte portuguesa dos alvores de Quinhentos - Paulo Esmeraldo Catarino Lopes (Mélanges de la Casa de Velázquez)
In 1510, an anonymous nobleman servant of the 4th Duke of Braganza, D. Jaime, left Portugal for Italy to return only in 1517. On the basis of this travel, he later wrote an extensive and impressive account. One of the figures that holds his attention is Francis I of France. Although sparse, the outlined portrait of the then young ruler suggests, from various perspectives, the decisive role that he will play in European foreign policy in the early 16th century. It is, in essence, a case study, but the truth is that we are dealing with an excellent critical instrument to go beyond the «circumscribed» context of the case itself, addressing broader questions at the interpretive level, such as the contest for hegemony in 16th century Europe, the passage from Christendom to Europe of increasingly centralized national monarchies or even the growing autonomy in relation to Rome by the emerging powers of the West.